Tenth Oxford Conference Organized by the Oxford International Biomedical Centre (OIBC). Issue 3 (18th July 2005) - Grzywna, Zbigniew J.; Michalec, Anna
Abstract : A series of events organized at Mansfield College and Magdalen College School by Oxford International Biomedical Centre from March 29th to April 1st 2004, is reported. There were more than 60 active participants (speakers, moderators and discussants) plus the general audience. A special programme for the group of five youngsters from developing and restructuring countries, for the first time in the 10 years history of OIBC conferences, was also run.